Value foundations of experiencing stress and adaptation of students: Cross-cultural study - E. I. Koltunov; V. G. Gryazeva-Dobshinskaya; Ya. A. Dmitrieva; N. V. Markina; J. Zhi; E. S. Naboichenko (Russian State Vocational Pedagogical University, 2022)
Introduction. Present work is dedicated to an urgent problem that has emerged as a result of a global trend - an increase in the number of young people moving to other countries in search for a higher education, which often leads to stress during the process of cultural adaptation.In the current research, the authors conducted a comparative analysis of the normative and individual values of students from China and Russia, studying at the Russian university. The relevance of the research is based on the existing need for distinguishing psychological resources that could be helpful in the process of cultural adaptation and experiencing stress during the contact with the new cultural environment. Value foundations are considered as one of such potential resources, capable of affecting process of experiencing stress and adaptation.The aim of the present article was to conduct a cross-cultural analysis of the normative and individual values of students from China, who experience stress and adapt to stressful situations in a new culture, and students from Russia studying with them.Methodology and research methods. The research uses a comparative analysis of values of different cultures and a complex analysis of value foundations in the context of experiencing stress and adaptation to stressful situations among migrant students.Results and scientifi novelty. In the course of the research, it was found out that values corresponding to the cultural specifi of the native countries of the students (China and Russia) are statistically more pronounced among students with a low level of stress. Among students with a high level of stress, values, which are not that part of the normative of their native culture, are more pronounced. Hedonistic values hamper the process of cultural adaptation both for Russian and Chinese students. A comprehensive study of the relationship between adaptation to stressful situations and stress experience revealed the groups of students with a cross-cultural specifiof the value foundations for experiencing stress. The data obtained both correlate with the existing studies of changes in values of students from China and Russia, and provide a basis for further research in the direction of studying stress and adaptation among students from both countries.Practical significance. The research results can be used in the analysis of stress exposure among students from Russia and China and the subsequent development of adaptational strategies. The discovered specificities of cultural value foundations could be employed to form potential resources of preadaptation to stressful situations among student youth.